KAJIAN TENTANG FIDES ALIENA DAN FIDES PROPRIA - Oktofianus Taebenu; Mozes Lawalata (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2026)
Abstract. This study is motivated by the theological debate concerning infant baptism within the Protestant tradition, particularly between the concept of fides aliena in the Reformed tradition and fides propria in the Anabaptist tradition. The primary issue addressed in this research lies in the differing foundations of faith confession underlying the practice of infant baptism and their implications for the church's understanding of faith, salvation, and the sacraments. This study aims to analyze the theological foundations of these two perspectives, explain the hermeneutical differences that shape them, and formulate their theological and pastoral implications for the contemporary church. The study employs a qualitative research method with a normative-critical theological approach and comparative-conceptual analysis. Data were collected through literature studies of the Bible, confessional documents, works of Reformed and Anabaptist theologians, as well as sources in historical and systematic theology. The findings reveal that the Reformed tradition views infant baptism as a communal sign of God's covenantal grace, whereas the Anabaptist tradition emphasizes baptism based on a conscious personal confession of faith. These differences arise from distinct approaches to hermeneutics, ecclesiology, and covenant theology. This study concludes that the church needs to understand baptism from historical, biblical, and pastoral perspectives in order to foster a dialogical attitude and a more responsible formation of faith. Keywords: Fides Aliena, Fides Propria, Infant Baptism, Reformed Theology, Anabaptism, Sacrament of Baptism